Boosting Students’ ESP Vocabulary by Utilizing AI Chatbot - Silitonga, Lusia Maryani; Wiyaka, Wiyaka; Prastikawati, Entika Fani (ETERNAL (English Teaching Journal), 2024)
Technology integration in foreign language learning is a must today. One of the issues is the utilization of artificial intelligence (AI) Chatbot in English language teaching. Some studies have mentioned the benefits and advantages of using AI Chatbot. Nonetheless, none of the studies examines deeply on hoe ESP vocabulary. To fill the gaps, this study examines the effect of AI Chatbot especially Dialogflow enhanced the ESP vocabulary acquisition. The experimental comparison of two groups—an experience group and a control group—is the backbone of this study in order to accomplish that purpose. Both groups underwent pre-tests and post-tests to assess the effectiveness of utilizing AI chatbot in learning ESP vocabulary. The chatbot content was meticulously constructed to incorporate vocabulary features such as synonyms and concise explanations of word meanings. The study's findings revealed that utilizing chatbots significantly improves the acquisition of ESP vocabulary. It was found that students in the experimental group that used Dialogflow, a chatbot, performed better than students in the control group. To add, the study suggests that chatbots could be utilized in many situations to enhance language learning in general or in specific ESP courses. A chatbot provides a stimulating setting to facilitate positive interactions where the negotiation of meaning occurs explicitly, which appears to greatly benefit learners in advancing their second language lexical development.